Características pós-colheita de cocos verdes em diferentes estádios de desenvolvimento e estações climáticas - Kwiatkowski, Angela (2011)
In recent years, farmers in the Northwest of Paraná has been cultivating the coconut tree, seeking commercialization of water of the green fruit. In literature there are few reports on production and quality of coconut in the region, because they are few producers who were motivated to produce fruit. In order to investigate the quality of coconut water and fresh fruit was produced this work. The fruits, cv. Dwarf Green, were collected from the Umuarama and Cidade Gaúcha cities, located in Northwest region of Paraná, in the four seasons and five stages. The evaluated fruit physical and chemical, biochemical and sensory characteristics of fresh coconut water. The results were evaluated by analysis of variance and means compared by Tukey test (p <0.05). The values of the climatic stations were evaluated with few variables outside of what the culture needs for production. The results indicated that the fruits showed an increase in fruit size and weight and volume of water, as increased time of fruit development in all seasons. The physical-chemical aspects indicate difference between the samples taken between seasons. The mass and size of coconuts and coconut water volume increased with increasing time of development, in all seasons in both locations. Turbidity statistical difference between the fruits, presenting the best value for water extracted fruit with five and six months of production Umuarama. The chemical composition indicates that coconut water collected after the winter season in both locations, have lower specifications in some parameters, in relation to water from fruits harvested at the end of the other stations. The enzyme activity had increased as increasing stage of fruit development. Sensory evaluation indicated better acceptance of the fruit of the fruits of seven months. xiii The acceptance of coconut water showed significant differences between the time of harvesting for the production of both cities, especially those harvested in late summer and spring. Despite the climate of the region evaluated undergo several changes during the year, with stations that have high variation in climatic conditions, and these may influence the production of coconut, fruit quality for the consumption of coconut water is approaching the fruits produced in the tropical regions.